Stiffness Requirements for Longitudinal Stiffeners of Trapezoidal Box Girder Bottom Flanges - Malik, Hawraa Sami; Jawad, David A. M. (Basrah Journal for Engineering Sciences, 2022)
The reason for the widespread use of steel box girders is that they have high structural efficiency due to the high bending, high torsional stiffness and rapid erection. For bottom flange of the girders, the buckling behavior during production and erection due to compression strength can be a problem. The compression plate with longitudinal stiffeners typically renders an economic. The optimal design of longitudinal stiffeners is discussed. The results are based on 3-D FEA (ANSYS19.2) of many stiffened compression bottom flange models, the moment of inertia requirement of bottom flange longitudinal stiffener is investigated by studying the effect of many parameters as longitudinal stiffeners numbers, stiffener sections, plate aspect ratio and compression flange thickness. Also, the stiffeners effect on the compression panel plate stresses were studied by modeling girder with and without longitudinal stiffeners. The finite element method is useful as they can be used to study the plate with stiffeners in an economical way, and we don’t need experimental and laboratory tests.